PENGARUH BIAYA PROMOSI TERHADAP VOLUME PENJUALAN PADA PT. IMA MONTAZ SEJAHTERA LHOKSEUMAWE - STIE Lhokseumawe (Sekolah Tinggi Ilmu Ekonomi Lhokseumawe, 2018)
This purpose of this research is to find the influence of promotion cost to sales volume in PT. Ima Montaz Sejahtera Lhokseumawe. Used data in this research was secondary data since the 2014-2016. Model regression analysis linear simple. The results of the study found that the value of the regression coefficient show the relation promotion cost positive give significance that every the increasing promotion then caused the sales of volume rose assuming other variables constant. For fear of a promotio cost volume of sales of goods he would do to PT. Ima Montaz Sejahtera Lhokseumawe. This research result indicates that with promotion cost issued by PT. Ima Montaz Sejahtera Lhokseumawe increase sales volume, however more firm consider the high cost for the promotion of the use of the company to produce profits based on target.